Biologia floral em moranga (Cucurbita maxima Duch. var. Exposição) - Nicodemo, Daniel [UNESP] (2007)
In order to study pumpkin floral biology (Cucurbita maxima) var. Exposição, were conduced two tests, using 128 plants, in 2,000 m². The opening and the withering of the flowers happened, on average, 6p5 and 13h52, respectively. There were, on average, 2.26 male flowers for each female flower. The female flowers produced, on average 138.9% more nectar than the male ones. The nectar production was smaller in the second test because of a lesser due precipitation and smaller relative humidity of the air. The sugar concentration in the nectar was 0.3 and 3.8% larger in the female flowers in relation to the male ones, respectively for the 1st and 2nd tests. The male flowers produced 129,021 pollen grains for flower, with 91.2% viable at 9h00. The stigma of the female flowers was receptive to the pollen grains, on average, to the 13p0. The female flowers were more attractive than the male ones.